Enantioselective syntheses of (R)-pipecolic acid, (2R,3R)-3-hydroxypipecolic acid, beta-(+)-conhydrine and (-)-swainsonine using an aziridine derived common chiral synthon - Chavan, Subhash P.; Khairnar, Lalit B.; Pawar, Kailash P.; Chavan, Prakash N.; Kawale, Sanket A. (RSC Advances, 2015)
Concise total syntheses of (R)-pipecolic acid, (R)-ethyl-6-oxopipecolate, (2R, 3R)-3-hydroxypipecolic acid and formal syntheses of beta-(+)-conhydrine, (-)-lentiginosine, (-)-swainsonine and 1,2-di-epi-swainsonine have been accomplished starting from a common chiral synthon. The present strategy employs regioselective aziridine ring opening, Wittig olefination and RCM as the key chemical transformations.